1978
DOI: 10.1172/jci108974
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Mechanism of Reduced Urinary Osmolality after Exposure of the Renal Papilla

Abstract: A B S T R A C T Studies were performiied in MlunichWistar rats to determine whether chaniges in papillary plasma flow might be responsible for the conicentrating defect which occurs after exposure of the extrarenal papilla. Papillary plasma flow was measured by 1251_ albumin accutnmulation. Initial studies in hydropenic animals revealed that papillary plasma flow was 40% higher in the kidney with the exposured papilla, 41 vs. 29 ml/min per 100 g of papilla (P < 0.001). This increase in papillary plasma flow wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

1979
1979
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 21 publications
2
29
1
Order By: Relevance
“…Whatever the true explanation for the role of the ureter in the concentrating mechanism, our results affirm that the continuity of the ureter is essential (1,3,6,8). It may be that rather than supplying solute to or removing water from the papilla, the intact ureter prevents the loss of solute from the hyperosmotic papilla.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Whatever the true explanation for the role of the ureter in the concentrating mechanism, our results affirm that the continuity of the ureter is essential (1,3,6,8). It may be that rather than supplying solute to or removing water from the papilla, the intact ureter prevents the loss of solute from the hyperosmotic papilla.…”
Section: Discussionsupporting
confidence: 70%
“…The specific contribution of the terminal collecting duct to urinary concentration has been assessed by micropuncture of the exposed renal papilla of rodents (1)(2)(3)(4)(5). Unfortunately, excision of the overlying ureter results in a substantial reduction (onethird or more) in urinary osmolality, a phenomenon attributed to interruption of the bathing of the papilla by urine (specifically, interruption of pelvic urea recycling) (6)(7)(8) or increased medullary blood flow with "washout" of medullary solute (3). Recently, Reinking and Schmidt-Nielsen (9) have redirected attention to Steinhausen's observation (10) of bolus, or intermittent flow, in the terminal collecting duct associated with ureteral peristalsis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, while a prostaglandin E-mediated decrease in collecting duct water permeability may have played a role, other factors may also be important. Recent studies from our laboratory have demonstrated that increased medullary blood flow can be associated with a decrease in urine osmolality (13). Since previous studies have noted that the medullary solute falls during bradykinin and acetylcholine administration, it may be that the decrease in medullary solute associated with the increase in papillary flow is the primary explanation for the decrease in urine osmolality observed during bradykinin administration.…”
Section: Discussionmentioning
confidence: 89%
“…Mongrel dogs, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] kg, were deprived of food and water for 12 h before study. Anesthesia was induced with intravenous sodium pentobarbitol, 30 mg/kg and a constant level of anesthesia was maintained by using additional 5-mg injections as needed.…”
Section: Methodsmentioning
confidence: 99%
“…Chuang and co-workers (17) suggested that exposure of the papilla stimulates the synthesis of prostaglandin E2, which increases papillary blood flow, causing washout of papillary solute. Reinking and Schmidt-Nielsen (18) that in antidiuresis, the papillary collecting ducts regularly open and close with a periodicity coincident with ureteral peristalsis and proposed that ureteral contraction stops flow periodically not only in the collecting ducts but in the loops of Henle and vasa recta as well.…”
Section: Discussionmentioning
confidence: 99%